Pediatric acute liver failure: Etiology, outcomes, and the role of serial pediatric end‐stage liver disease scores. (16th April 2013) - Rajanayagam, Jeremy; Coman, David; Cartwright, David; Lewindon, Peter J.
Abstract To describe etiology, short‐term outcomes and prognostic accuracy of serial PELD scores in PALF. Retrospective analysis of children aged ≤16 yr, admitted with PALF under the QLTS, Brisbane, Australia, between 1991 and 2011. PELD‐MELD scores were ascertained at three time points (i) admission (ii), meeting PALF criteria, and (iii) peak value. Fifty‐four children met criteria for PALF, median age 17 months (1 day–15.6 yr) and median weight 10.2 kg (1.9–57 kg). Etiology was known in 69%: 26% metabolic, 15% infective, 13% drug‐induced, 6% autoimmune, and 9% hemophagocytic lymphohistiocytosis. Age <3 months and weight <4.7 kg predicted poor survival in non‐transplanted children. Significant independent predictors of poor outcome (death or LT) were peak bilirubin > 220 μm/L and peak INR > 4. Serial PELD‐MELD scores were higher in the 17 (32%) transplant recipients (mean: [i] 26.8, [ii] 31.8, [iii] 42.6); highest in the 12 (22%) non‐transplanted non‐survivors (mean: [i] 31.6, [ii] 37.2, [iii] 45.7) compared with the 25 (46%) transplant‐free survivors (mean: [i] 25.3, [ii] 26.0, [iii] 30.3). PELD‐MELD thresholds of ≥27 and ≥42 at (ii) meeting PALF criteria and (iii) peak predicted poor outcome (p < 0.001). High peak bilirubin and peak INR predict poor outcome and serial PELD‐MELD is superior to single admission PELD‐MELD score for predicting poor outcome.